Perceived Burdensomeness and the Wish for Hastened Death in Persons With Severe and Persistent Mental Illness - Stoll, Julia; Ryan, Christopher James; Trachsel, Manuel (Frontiers in Psychiatry, 2021)
Background: In several European countries, medical assistance in dying (MAID) is no longer confined to persons with a terminal prognosis but is also available to those suffering from persistent and unbearable mental illness. To date, scholarly discourse on MAID in this population has been dominated by issues such as decision-making capacity, uncertainty as to when a disease is incurable, stigmatization, isolation, and loneliness. However, the issue of perceived burdensomeness has received little attention. Objective: The study explores the possible impact of perceived burdensomeness on requests for MAID among persons with severe and persistent mental illness (SPMI). Method: Using the method of ethical argumentation, we discuss the issue of access to MAID for persons with SPMI and perceived burdensomeness. Conclusion: Perceived burdensomeness may be a contributing factor in the wish for hastened death among persons with SPMI. MAID is ethically unsupportable if SPMI causes the individual to make an unrealistic assessment of burdensomeness, indicating a lack of decision-making capacity in the context of that request. However, the possibility that some individuals with SPMI may perceive burdensomeness does not mean that they should be routinely excluded from MAID. For SPMI patients with intact decision-making capacity who feel their life is not worth living, perceived burdensomeness as a component of this intolerable suffering is not a sufficient reason to deny access to MAID.